PENGARUH KEMAMPUAN TEKNOLOGI INFORMASI KOMUNIKASI, SARANA PRASARANA, DAN KOMPETENSI PROFESIONAL GURU TERHADAP MUTU PENDIDIKAN SD NEGERI SE KECAMATAN TODANAN KABUPATEN BLORA - Muntamah, Siti; Kusumaningsih, Widya; Soedjono, Soedjono (Dharmas Education Journal (DE_Journal), 2024)
This research aims to determine the magnitude of the influence of information communication technology capabilities, infrastructure and professional competence of teachers on the quality of public elementary school education in Todanan District, Blora Regency. This research uses a quantitative research approach and an ex post facto type of research. The research population was all state elementary school teachers in Todanan District, Blora Regency. The total research sample was 208 teachers. Research analysis includes simple regression analysis and multiple regression analysis. The research results are: (1) there is an influence of information communication technology capabilities on the quality of education of 30.6% with the regression equation Y = 51.763 + 0.686X1; (2) there is an influence of infrastructure on the quality of education of 31.8% with the regression equation Y = 54.529 + 0.490X2; (3) there is an influence of teacher professional competence on the quality of education of 35.7% with a regression equation of 46.594 + 0.790X3; and (4) there is an influence of information communication technology capabilities, infrastructure and teacher professional competence on the quality of education of 49.5% with the regression equation Y = 12.149 + 0.387X1 + 0.198X2 + 0.446X3.